BEYOND THE WHITE COAT: NAVIGATING STRESS AND COPING STRATEGIES IN A MEDICAL COLLEGE OF KARACHI - FATIMA , A; KHURSHEED , I; ALAM , SN (Biological and Clinical Sciences Research Journal, 2023)
An analytical correlational study was conducted at a university in Karachi from June 2021 to December 2021 to evaluate stress levels and types of specific coping strategies medical students adopt. All first- and third-year MBBS program students were included in the study. Depression, Anxiety, and Stress Scale – 21 (DASS 21) was used to measure psychological variables. Coping strategies were evaluated through the Brief Cope Scale. The total number of students who filled out both questionnaires was 96 in the first year and 89 in the third year, with a response rate of 64%, and 59.3% respectively. The percentage of students whose stress level ranges from mild to extremely severe was 50% in the first year and 34.83% in the third Year. The three most common coping strategies used by first-year students were religion, acceptance, and self-blame, while those used by third-year students were religion, acceptance, and active coping. It can be concluded that medical students have high-stress levels and use varying coping strategies to adapt and settle.